The Political Career of Maria Ullfah 1934-1947 - Masrokah Masrokah; Siti Masykuroh; Uswatun Hasanah (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study examines the political career of Maria Ullfah from 1934 to 1947, as well as the influence of her family and education on the formation of her political consciousness. Born into an educated priyayi family, Maria Ullfah had access to extensive formal education from an early age, eventually pursuing legal studies at Leiden University in the Netherlands. Growing up in a family environment closely connected to intellectual traditions and the colonial bureaucracy, combined with her experiences witnessing injustices against women, nurtured her social sensitivity and early commitment to gender equality. Her Western education and interactions with figures of the national movement, such as Sutan Sjahrir, further strengthened her awareness as part of a colonized nation in need of change. Upon returning to Indonesia, she actively participated in women’s organizations, educational institutions, and the national movement, playing a key role in the Indonesian Women’s Congress, KOWANI, and literacy eradication efforts. During the revolutionary period, her intellectual capacity and dedication led to her being appointed a member of the BPUPKI and later becoming the first female Minister of Social Affairs. Her contributions not only opened public spaces for women but also played a significant role in the political processes leading to the establishment of the Indonesian state. This study demonstrates that family background, education, and personal experiences were significant factors in shaping Maria Ullfah as a central figure in the women’s movement and the struggle for independence.